ANALYSIS OF THE OPTIMAL PRODUCTION AREA IN METAL CASTING PT. SUYUTI SIDO MAJU KLATEN - Purnama, Angga; Lastari, SE., MM, Siwi; Darini, M.Si., Dra. Sri (Management, 2010)
This study aims to (1) know the size of the optimal production volume, (2) know the level of maximum benefit to be obtained. This study uses linear programming analysis of simplex method with samples of products and equipment manufactured by companies that are the products of companies that rate high enough sales. Place this research is done in PT. Suyuti Sido Maju Klaten District Advancement and time in October 2005 to March 2006. The object that is broad optimum production and maximum profit. Collecting data in this study using interviews, observation and documentation. Analysis of the data used is the quantitative approach. The results of this study indicate: (1). According to mathematical calculations by using the Analysis of Linear Programming Simplex Method, a combination of products produced by PT.Suyuti Sido Maju reaching optimum production namely: End Bracked 300F (X1) = 700 units, Discharge Elbow (x2) = 1450 units, ejector Casing (X3) = 6500, 225 Bearing Cover (x4) = 6875 units, Fan 23 (X5) = 675 units. (2). Area of production that can provide profit / maximum profit for PT.Suyuti Sido Maju in 2005 is Rp. 214,937,500.00, excess cost advantage / profit conventionally and according to the Simplex Method is Rp. 17,737,500.00 Keywords : Production, metal.